Being a Foster-to-Adopt Parent: Experiences of (Un)certainty and Their Influence on the Sense of Being the Parent. Issue 2 (3rd April 2019) - Pagé, Geneviève; Poirier, Marie-Andrée; Chateauneuf, Doris
Abstract: The Mixed-Bank Program (Quebec, Canada) is based on concurrent planning principles. While the primary goal of this placement is reunification of the child with their birth parents, the low probability of this happening calls for simultaneously planning for an alternative solution, such as adoption. As a result, foster-to-adopt families have to deal with the uncertainty of the adoptability of the child and having no legal status nor control over the situation. In a qualitative study focusing on understanding how foster families from the Mixed-Bank Program develop the sense of being the parent of the child they care for, 25 semi-structured interviews with foster parents from 20 different families were conducted. As part of grounded theory methodology, a typology of profiles according to the level of uncertainty was constructed: (1) experience of certainty, (2) experience of momentary uncertainty, and (3) chronic uncertainty. This article presents these profiles and discusses the following challenges: the willingness to settle for permanence without adoption in all profiles, the link between the level of uncertainty and the assiduity of birth parents to supervised visits with the child, and the lack of power and control over the fulfillment of the goal of having or completing a family.